Educational issues in Mahua fictions (1934-1999) - Leong, Soo Yen (2013)
Chinese education in Malaysia began in the early 19th century. Since then, Chinese education has been an integral part of the Chinese community in Malaysia. It transmits the language and culture and therefore plays a vital role in the Chinese community. The Chinese community were of the utmost concerned about the development of their mother tongue education. From the establishment of Chinese education up till now, it has all along gone through many obstacles and setback until what it has been preserved today. During this period, whatever hardships that the Chinese education went through have become the inspiration of writing for Malaysian writers in Chinese. Since early 19th century, Chinese who came to Malaya as teachers used to write fictions based on local educational issues, together with their own observations and experiences. They had created a significant number of works that reflected the problems encountered by the Chinese education. After independence, in order to preserve the mother-tongue education, the writers created many works that further reflected the voice of the Chinese community i.e. the struggles, hardships and their pains. The writings were likening to perpetuate the Chinese culture. Mahua fictions further emphasized the points above. This study analyses the issues of Chinese education in the fictions in order to understand the social and cultural problems faced by the community. The period of this study started from 1934-1999, through the analysis of the subject content of these fictions, the Chinese education issues in the Mahua fictions in the 20th century are studied. This thesis consists of five chapters. The first chapter is the introduction; the second chapter outlines an overview of the writing of educational issues in Mahua fictions. The following third and fourth chapters reveal the objective and subjective factors that closely related to the Chinese education in Mahua literature. The fifth chapter is the conclusion of the thesis. The study found that the problem of education in the 20th century seen in Mahua fiction prevail that the relationship between Chinese education and Chinese literature are inseparable and closely related one to another. The problems of Chinese education in Malaysia are clearly reflected in Mahua fictions with themes of educational issues, and it seems to be a microcosm of the development of Chinese education in Malaysia.